Interventions Designed to Promote Exclusive Breastfeeding in High-Income Countries: A Systematic Review Update - Skouteris, H.; Bailey, C.; Nagle, C.; Hauck, Yvonne; Bruce, L.; Morris, H. (Mary Ann Liebert, Inc. Publishers, 2017)
Background: Worldwide, women seldom reach the recommended target of exclusive breastfeeding up to 6 months postpartum. The aim of the current study was to update a previously published review that presented a conceptual and methodological synthesis of interventions designed to promote exclusive breastfeeding up to 6 months in high-income countries. Materials and Methods: A systematic search of leading databases was conducted for scholarly, peer-reviewed, randomized controlled trials published from June 2013 to December 2016. Twelve new articles were identified as relevant; all were published in English and assessed exclusive breastfeeding with a follow-up period extending beyond 4 months postpartum. Articles were analyzed for overall quality of evidence in regard to duration of exclusive breastfeeding, using the Grading and Recommendations Assessment, Development, and Evaluation approach. Results: A significant increase in the duration of exclusive breastfeeding was found in 4 of the 12 studies. All four successful interventions had long-duration postpartum programs, implemented by telephone, text message, or through a website. Some of the successful interventions also included prenatal education or in-hospital breastfeeding support. Conclusions: Results from this review update correspond closely with previous findings, in that all of the successful interventions had lengthy postnatal support or an education component. More studies assessed intervention fidelity than in the previous review; however, there was little discussion of maternal body–mass index. While a pattern of successful interventions is beginning to emerge, further research is needed to provide a robust evidence base to inform future interventions, particularly with overweight and obese women.